Contralaterally EMG-triggered functional electrical stimulation during serious gaming for upper limb stroke rehabilitation: a feasibility study - Höhler, Chiara; Wild, Laura; de Crignis, Alexandra; Jahn, Klaus; Krewer, Carmen (Frontiers in Neurorobotics, 2023)
Introduction Virtual Reality/serious games (SG) and functional electrical stimulation (FES) therapies are used in upper limb stroke rehabilitation. A combination of both approaches seems to be beneficial for therapy success. The feasibility of a combination of SG and contralaterally EMG-triggered FES (SG+FES) was investigated as well as the characteristics of responders to such a therapy. Materials and Methods In a randomized crossover trial, patients performed two gaming conditions: SG alone and SG+FES. Feasibility of the therapy system was assessed using the Intrinsic Motivation Inventory (IMI), the Nasa Task Load Index, and the System Usability Scale (SUS). Gaming parameters, fatigue level and a technical documentation was implemented for further information. Results In total, 18 patients after stroke (62.1±14.1 years) with a unilateral paresis of the upper limb (MRC≤4) were analyzed in this study. Both conditions were perceived as feasible. Comparing the IMI scores between conditions, perceived competence was significantly increased (z=-2.88, p=.004) and pressure/tension during training (z=-2.13, p=.034) was decreased during SG+FES. Furthermore, the task load was rated significantly lower for the SG+FES condition (z=-3.14, p=.002), especially the physical demand (z=-3.08, p=.002), while the performance was rated better (z=-2.59, p=.010). Responses to the SUS and the perceived level of fatigue did not differ between conditions (SUS: z=-0.79, p=.431; fatigue: z=1.57, p=.115). For patients with mild to moderate impairments (MRC 3-4) the combined therapy provided no or little gaming benefit. The additional use of contralaterally controlled FES (ccFES), however, enabled severely impaired patients (MRC 0-1) to play the SG. Discussion The combination of SG with ccFES is feasible and well accepted among patients after stroke. It seems that the additional use of ccFES may be more beneficial for severely impaired patients as it enables the execution of the serious game. These findings provide valuable implications for the development of rehabilitation systems by combining different therapeutic interventions to increase patients’ benefit and proposes system modifications for home use. The study was registered with the German Clinical Trials Register (https://drks.de/search/en; registration number: DRKS00025761).